Institutionalization or Decoupling? An Exploratory Analysis of the UN Global Compact LEAD Initiative. (2nd December 2015) - Junaid, Nora; Leung, Opal; Buono, Anthony F.
Abstract: Institutionalization occurs when organizations adopt policies and practices in an attempt to increase their legitimacy and competitive position. This process assumes that an organization's formal policies (macro‐level) are translated into organizational practices (micro‐level). This translation, however, can fail to occur, resulting in organizational decoupling and de‐institutionalization. Drawing on an institutionalization typology based on different levels of legitimacy (macro) and taken‐for‐grantedness (micro), the article draws on data from an assessment of the United Nations Global Compact LEAD initiative, assessing the extent to which this initiative is being institutionalized in the member firms and examining the implications for the LEAD initiative and our thinking about institutionalization.